A NR2E1‐interacting peptide of LSD1 inhibits the proliferation of brain tumour initiating cells. Issue 1 (2nd November 2022) - Hu, Rong; Hameed, Umar Farook Shahul; Sun, Xiang; Moorthy, Balakrishnan Shenbaga; Zhang, Wen; Jeffrey, Philip D.; Zhou, Li; Ma, Xin; Chen, Fangjin; Pei, Jianfeng; Giri, Pankaj K.; Mou, Yonggao; et al.
Abstract: Objectives: Elimination of brain tumour initiating cells (BTICs) is important for the good prognosis of malignant brain tumour treatment. To develop a novel strategy targeting BTICs, we studied NR2E1(TLX) involved self‐renewal mechanism of BTICs and explored the intervention means. Materials and Methods: NR2E1 and its interacting protein‐LSD1 in BTICs were studied by gene interference combined with cell growth, tumour sphere formation, co‐immunoprecipitation and chromatin immunoprecipitation assays. NR2E1 interacting peptide of LSD1 was identified by Amide Hydrogen/Deuterium Exchange and Mass Spectrometry (HDX‐MS) and analysed by in vitro functional assays. The in vivo function of the peptide was examined with intracranial mouse model by transplanting patient‐derived BTICs. Results: We found NR2E1 recruits LSD1, a lysine demethylase, to demethylate mono‐ and di‐methylated histone 3 Lys4 (H3K4me/me2) at the Pten promoter and repress its expression, thereby promoting BTIC proliferation. Using Amide Hydrogen/Deuterium Exchange and Mass Spectrometry (HDX‐MS) method, we identified four LSD1 peptides that may interact with NR2E1. One of the peptides, LSD1‐197‐211 that locates at the LSD1 SWIRM domain, strongly inhibited BTIC proliferation by promoting Pten expression through interfering NR2E1 and LSD1 function. Furthermore, overexpression of this peptide in human BTICs can inhibit intracranial tumour formation. Conclusion: Peptide LSD1‐197‐211 can repress BTICs by interfering the synergistic function of NR2E1 and LSD1 and may be a promising lead peptide for brain tumour therapy in future. Abstract : NR2E1 and LSD1 complex directly represses Pten in BTICs by demethylating H3K4me and H3K4me2 at its promoter, and thus promotes the proliferation of BTICs. LSD1‐197‐211 peptide interferes the interaction between NR2E1 and LSD1 and restores Pten expression, which in turn inhibits the proliferation of BTICs.